Warfarin, acetylsalicylic acid and risk of incident atrial fibrillation in patients with heart failure and sinus rhythm : a meta-analysis - Caldeira, Daniel (2018)
Copyright © 2013 Elsevier Ireland Ltd. All rights reserved.